Fluorinated hexagonal boron nitride as a spacer with silver nanorods for surface enhanced Raman spectroscopy analysis. Issue 5 (1st March 2021) - Ahmad, Aqrab ul; Abbas, Qasim; Ali, Sajid; Fakhar-e-alam, Muhammad; Farooq, Zahid; Farid, Amjad; Abbas, Akmal; Javid, Muhammad; Muhammad Afzal, Amir; Umair Arshad, Hafiz Muhammad; Iqbal, Muzammil
Abstract: This manuscript presents a unique SERS substrate consisting of different number of silver nanorods (AgNRs) layers with fluorinated hexagonal boron nitride nanosheets (F-BN) as a spacer. The presentation of fabricated SERS nanostructure was examined and found that the SERS effect has been amplified by increasing the number of AgNRs layers. Sensitivity of SERS substrates was also examined by calculating the enhancement factor (EF) and limit of detection (LOD) down to concentrations 10 −12 and 10 −11 for the targeted dyes rodamine (R6G) and crystal violet (CV), respectively. Our results demonstrated that SERS performance of proposed nanostructure can be ascribed due to the production of topmost hot spots on AgNRs layers. It is believed that stronger electromagnetic field might be generated at the tapering gap between AgNRs and F-BN layers which brings out a higher EF and superior detection limit. Consequently, it is hoped that the concept of usage of F-BN as spacer with plasmonic materials for the fabrication of SERS can broadly be employed to improve SERS sensitivity and detection capability for variety of targeted analytes.